2013
DOI: 10.1111/dsu.12078
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Vertical Pathology of Debulking Specimens During Mohs Micrographic Surgery for Lentigo Maligna and Melanoma in Situ

Abstract: When performing MMS for LM or MIS, it is appropriate and necessary to send the central debulking specimen for permanent histology for accurate tumor staging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 21 publications
3
27
1
Order By: Relevance
“…Iorizzo et al . found that 8·1% of lentigo maligna and melanoma in situ , diagnosed on biopsy, were invasive melanoma after examination of excision specimen . In our series, five of 100 lesions (5%) diagnosed as lentigo maligna were diagnosed as lentigo maligna melanoma after excision.…”
Section: Discussionmentioning
confidence: 41%
“…Iorizzo et al . found that 8·1% of lentigo maligna and melanoma in situ , diagnosed on biopsy, were invasive melanoma after examination of excision specimen . In our series, five of 100 lesions (5%) diagnosed as lentigo maligna were diagnosed as lentigo maligna melanoma after excision.…”
Section: Discussionmentioning
confidence: 41%
“…In the author's experience, skip areas have been occasionally observed but the true incidence is unknown. Overall, the rate of upstaging from LM to invasive disease upon final excision (11.7%) was high but within the expected range compared with other recently reported rates of upstaging for LM and melanoma in situ (4-11.7%) [15,[19][20][21]. Thus, the prior cosmetic treatment did not appear to have an effect on overall prognosis, but the wider surgical margins resulted in larger defects creating reconstructive challenges and increased morbidity.…”
Section: Discussionsupporting
confidence: 51%
“…On the other hand, it is also possible that there may be an underestimation of the cumulative risk of LMM after LM, because LM is normally treated in the Netherlands, which would decrease the risk of progression. Also, some of the LM diagnosed as an in situ lesion by initial biopsy or conventional excision may have already had an unrecognized component of dermal invasive melanoma and were actually representing LMM (Abdelmalek et al, 2012;Hazan et al, 2008;Iorizzo et al, 2013). Finally, LMM registered without a previous diagnosis of LM would not have been included in our analysis and may also have resulted in an underestimation.…”
Section: Discussionmentioning
confidence: 99%